G58(P) A National Audit of Parenteral Nutrition Practise in UK Neonatal Intensive Care Units: Is Practise Consistent with Guidelines?. (4th June 2013) - Glynn, A; Barr, S; Lewis, A; Tuthill, DP
Abstract : Background: Parenteral nutrition (PN) is a lifesaving modality providing vital nutrients for neonates unable to tolerate enteral feeding. It has serious complications, including metabolic derangements, infection and line displacements which can be fatal. Positive outcomes can be maximised and complications minimised by appropriate biochemical monitoring, multidisciplinary involvement, adherence to evidence based clinical guidelines and careful venous line management. Objective: To audit current PN practises in all UK neonatal units against ESPGHAN European guidelines 2005 on protein and lipid introduction, American clinical guidelines for hyperglycaemia and hypoglycaemia in neonates receiving PN 2012, and the UK National Confidential Enquiry into Outcome and Death (NCEPOD) recommendations 2010 for venous access. Methods: A questionnaire was devised by a pharmacist, paediatrician and neonatologist. Questions focused on key areas commonly encountered in routine PN practise, for which guidance is available. These included protein and lipid introduction, monitoring and complications of lipids, management of hyperglycaemia and venous access. One researcher conducted a telephone survey to registrars working in all 58 level 3 neonatal intensive care units (NICU) throughout the UK. Results: The response rate was 58/58 units (100%). For preterm neonates requiring PN, protein is commenced on day 1 in 88% of units and lipids by day 3 in 91%. Most units exclusively use central lines for PN administration. All units use x-ray verification of catheter tip position with 19 units also using contrast. Triglyceride levels are not monitored in 22 units. Management of hyperglycaemia is variable, with 25 units using insulin first line and not altering glucose infusion. Seven units avoid insulin use completely. Conclusion: Many nutritional support practises were consistent and in line with guidelines. However over a third of units fail to monitor triglyceride levels despite the known consequences of high lipid infusions and recommendations for monitoring. The high usage of insulin in the management of hyperglycaemia may not be advantageous considering recent findings around the risks of hypoglycaemia and mortality. The use of contrast for line verification is not nationally standardised.